Peran Teknologi Pendidikan dalam Meningkatkan Daya Saing Pendidikan di MTsN 1 Sijunjung - Alwis, Dona Ana Yori; Turrohma, Mitra; Fazis, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study examines the role of technology in increasing educational competitiveness in MTsN 1 Sijunjung. In the era of globalization and the industrial revolution 4.0, technology has become an important component in the educational process. This study aims to determine the role of educational technology in improving educational competitiveness in MTsN 1 Sijunjung.This study uses a qualitative method with data collection through observation, interviews, and document analysis. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the study show that the use of technology such as computers, internet, and educational software in MTsN 1 Sijunjung has had a positive impact on students' learning motivation, teaching effectiveness, and students' ability to face competitive challenges in the future. However, the study also identified several obstacles, such as limited technological infrastructure and lack of training for teachers. Therefore, it is recommended that schools and local governments increase investment in technology infrastructure and training programs to maximize the potential of technology in education. In conclusion, technology has a significant role in increasing the competitiveness of education in MTsN 1 Sijunjung, but there is a need for continuous support to overcome various existing challenges